Photosynthetic, antioxidative, and metabolic adjustments of a crop plant to elevated levels of La and Ce exposure - Erkai He; Willie J.G.M. Peijnenburg; Hao Qiu (Ecotoxicology and Environmental Safety, 2022)
Rare earth elements (REEs) have been widely applied as fertilizers in farmland of China for decades to improve the yield and quality of crops. Unfortunately, adverse effects on plants have been observed due to overdosing with REEs. Until now, the toxicology of REEs was mainly evaluated based on phenotypic responses, but knowledge gaps still exist concerning their metabolic effects. Here, the physiological responses and nontargeted metabolomics studies were combined to systematically explore the potential effects of La and Ce on a crop plant, wheat Triticum aestivum. It was observed that REEs accumulated in the shoots of wheat, with significant reduction of the shoot biomass at higher exposure doses. The disturbance of photosynthesis and induced oxidative stress were identified by analyzing indicators of the photosynthetic (chlorophyll a/b, carotenoid and rubisco) and antioxidant systems (POD, CAT, SOD, GSH and MDA). Furthermore, the global metabolic profiles of REEs treatment groups and the non-exposed control group were screened and compared, and the metabolomic disturbance of REEs was dose-dependent. A high overlap of significantly changed metabolites and matched disturbed biological pathways was found between La and Ce treatments, indicating similarity of their toxicity mechanism in wheat shoots. Generally, the perturbed metabolomic pathways were mainly related to carbohydrate, amino acid and nucleotide/side metabolism, suggesting a disturbance of carbon and nitrogen metabolism, which finally affected the growth of wheat. We thus proved the potential adverse effect of inappropriate application of REEs in crop plants and postulated metabolomics as a feasible tool to identify the underlying toxicological mechanisms.